Replica Plating Method for Estimating Phenanthrene-Utilizing and Phenanthrene-Cometabolizing Microorganisms - Shiaris, Michael P. (1983)
A replica plating method was developed for detecting and enumerating phenanthrene-degrading microorganisms. The method is designed to discriminate between aquatic organisms that utilize phenanthrene as the sole carbon and energy source and organisms that cometabolize phenanthrene. The method was used to demonstrate that phenanthrene utilizers and phenanthrene cometabolizers coexist in estuarine sediments.